Iceland : Selected Issues. (IMF Staff Country Reports; Country Report, 1999)
This Selected Issues paper focuses on the European Monetary Union and the monetary policy framework in Iceland. It concludes that in terms of an exchange rate regime, the two most realistic options for Iceland are to continue with the existing arrangement or adopt a unilateral peg to the euro. However, it is argued that both options entail the need for enhancing the independence of the central bank, which will require reforming the Central Bank of Iceland Act. The paper also discusses a Scandinavian forecasting model for inflation in Iceland.